2016
DOI: 10.20546/ijcrar.2016.403.012
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Caries in First Permanent Molars in South West Coastal Population of India

Abstract: A B S T R A C TAim of the study was to analyse the prevalence of caries in first molars in south west coastal population in India. A total of 2000 patients were examined after obtaining the ethical clearance from the central ethical committee of NITTE University. Written consent was obtained and the patients who had caries on first molar teeth were questioned with a standard questionnaire to find its relation with age, gender, dietary habits and location. Data was recorded on prepared survey form based on WHO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
3
0
0
Order By: Relevance
“…Khalid H.M. et al had results similar to our results were there was no significance difference between caries in molars of girls and boys, as they found that of a total 432 children, 199 (46%) were male and 233(54%) were females [24] . In addition, the current study were comparable to the results reported by Sudhakaran et al, showed no significant difference was found between caries of FPMs in both genders as caries in girls represented 84.33% and caries in boys represented 83.35% [25] . Some studies recommended that, the use of fluoride and application of fissure sealants on newly erupted FPMs could lead to reduction of the prevalence of caries [26] .…”
Section: Discussionsupporting
confidence: 90%
“…Khalid H.M. et al had results similar to our results were there was no significance difference between caries in molars of girls and boys, as they found that of a total 432 children, 199 (46%) were male and 233(54%) were females [24] . In addition, the current study were comparable to the results reported by Sudhakaran et al, showed no significant difference was found between caries of FPMs in both genders as caries in girls represented 84.33% and caries in boys represented 83.35% [25] . Some studies recommended that, the use of fluoride and application of fissure sealants on newly erupted FPMs could lead to reduction of the prevalence of caries [26] .…”
Section: Discussionsupporting
confidence: 90%
“…The caries incidence were higher on right, left mandibular arch followed by right and left maxillary arch (FDI tooth number 36,46, 16, 26) yielded (27.0%, 28.6%, 23.1%, and 21.3% respectively). a similar results was observed in Istanbul, Turkey [23] , in Saudi Arabia [24] and in Pakistan [18] , South west coastal, India [25] . These finding may be due to mandibular FPMs erupts earlier than the maxillary, in addition the mandibular FPMs is exposed to oral environment for long period.…”
Section: Discussionsupporting
confidence: 87%
“…In Group A, the mandibular first permanent molars exhibit higher percentage of carious (6.8%) than the maxillary counterpart (5.7%). These findings are agreed with the results reported on Sudanese children, mandibular FPM exhibited higher caries incidence (76.5%) than maxillary counterpart (69.9%) [27] , in India, the total number of carious first molar was higher in the mandible than the maxilla [28] . Another studied in Saudi Arabia showed strong correlations between upper contra lateral FPMs (r=0.586) and lower Contra lateral FPMs (r=0.567, P< 0.001) [29] .…”
Section: Discussionsupporting
confidence: 92%